Effect of Poor Indoor Air Quality (IAQ): A Review - Mohamed Sunar, Norshuhaila; Parjo, Umi Kalthsom; Subramaniam, Menega; Leman, Abdul Mutalib (Penerbit UTHM, 2020)
Indoor air quality (IAQ) is defined as the quality of indoor air in the buildings and structures that influence to the building’s occupants’ health. Human exposure to indoor air pollutants is difficult to quantify as it is largely determined by micro-environmental characteristics. Pollution levels in one home may be quite different from those in another, depending on the occurrence and usage of sources of pollutants and on the ventilation habits. The presence chapter discussed about major effect of poor indoor air quality consequences of high pollution levels. Effects of indoor air pollution can be life threatening. Kids and old age people are more prone to the after effects of indoor air pollution.